CAHAYA SEBAGAI BENTUK SENI - Dendi Suwandi (Ars: Jurnal Seni Rupa dan Desain, 2007)
Light is always present around us and lightens every aspect o f our life. Nevertheless, we sometimesJorgct that light is a very unique material it can be seen but not touched. Moreover, it can, actually be used asan expressive media in creating artwork. Natural as well as artificial light such as from electricity, has beenexploited by light-artists to create their arhvorks over long periods o f time and with low intensity.Producing light art through the vision o f the colour o f light, the variation o f shadow, the lightreflection, the construction o f lamp-light, kinetic light and hologram as what some light-artists have done issupposed to inspire other artists in creating and developing tiezv light art.Light art does not mean forming certain shapes, or applying certain techniques which require hightechnology but, instead, applies simple techniques. It depends on our capability in treating and processingthe material as the expressive media. Yet, it cannot be denied that light art relates to an understanding aboutscience, art and technology which unites with thought and the process o f creation.Keywords: light, the colour o f light, shadow, reflection, light art